Fault‐tolerant control of inverter for the integration of solar PV under abnormal conditions. Issue 11 (13th November 2020) - Moradmand, Anahita; Dorostian, Mehrdad; Ramezani, Amin; Sajadi, Amirhossein; Shafai, Bahram
Abstract : Solar photovoltaic (PV) is a prominent technology for the generation of electricity and its utility is on the rise. The PV‐based generation facilities are susceptible to faults which if mismanaged, can result in an interruption in the supply of load demand and damage to the system. Faults in PV systems are caused by a broad range of reasons and hence, it is crucial to situate a fault‐tolerant system for reliable operation. This study proposes a fault‐tolerant control strategy for power electronics inverters for the integration of PV systems into power systems. This is a supervisory mechanism designed to aid PV systems to continue their operation during faults. A computer simulation verifies the performance of the proposed control strategy under a series of common fault conditions assuming a wide range of configurations for the PV system and load variations.